Surveying for engineers - Uren, J. (Palgrave Macmillan, 2010)
This classic engineering surveying text has been thoroughly updated to include recent developments in the field. New features focus on increasing accessibility for students, including updated illustrations, a new student-friendly text design, plus new pedagogical features within each chapter.